High Tolerance of Hydrogenothermus marinus to Sodium Perchlorate - Beblo-Vranesevic, Kristina; Huber, Harald; Rettberg, Petra (Frontiers in Microbiology, 2017)
On Mars, significant amounts (0.4 – 0.6 %) of perchlorate ions were detected in dry soil by the Phoenix Wet Chemistry Laboratory and later confirmed with the Mars Science Laboratory. Therefore, the ability of Hydrogenothermus marinus, a desiccation tolerant bacterium, to survive and grow in the presence of perchlorates was determined. Results indicated that H. marinus was able to tolerate concentrations of sodium perchlorate up to 200 mM (≙ 1.6 %) during cultivation without any changes in its growth pattern. After the addition of up to 440 mM (≙ 3.7 %) sodium perchlorate, H. marinus showed significant changes in cell morphology; from single motile short rods to long cell chains up to 80 cells. Furthermore, it was shown that the known desiccation tolerance of H. marinus is highly influenced by a pre-treatment with different perchlorates; additive effects of desiccation and perchlorate treatments are visible in a reduced survival rate. These data demonstrate that thermophiles, especially H. marinus, have so far, unknown high tolerances against cell damaging treatments and may serve as model organisms for future space experiments.